Evaluation of The Success of Career Guidance Program in Vocational High Schools (VHS) (International Journal of Active Learning, 2022)
This study aimed to evaluate the success of career guidance for students and administer an improved recommendation implemented by vocational schools in Yogyakarta, Indonesia. Data was collected from 978 students of 8 vocational schools using the questionnaire method. The validity test for instruments utilized an analysis factor by the assessment of SPPS and SmartPLS 3.0. The reliability test was also performed using Alpha Cronbach, with the career guidance success rate described and observed in the aspects requiring improvement. The result furthermore showed the success rate of career guidance reached an average of 80.86 of 100 in the very good category. However, the minimum standard of 100 recommended 50% of schools to increase the success rate of the program, and at 85 it was 87% improved. Some aspects required improvements such as career readiness in 6 schools at 75%, self-understanding in 7 schools at 87%, and career understanding in 8 schools at 100%, were obtained from data analysis.Â